Non-invasive Production of Multi-Compartmental Biodegradable Polymer Microneedles for Controlled Intradermal Drug Release of Labile Molecules - Battisti, Mario; Vecchione, Raffaele; Casale, Costantino; Pennacchio, Fabrizio A.; Lettera, Vincenzo; Jamaledin, Rezvan; Profeta, Martina; Di Natale, Concetta; Imparato, Giorgia; Urciuolo, Francesco; Netti, Paolo Antonio (Frontiers in Bioengineering and Biotechnology, 2019)
Transdermal drug delivery represents an appealing alternative to conventional drug administration systems. In fact, due to their high patient compliance, the development of dissolvable and biodegradable polymer microneedles has recently attracted great attention. Although stamp-based procedures guarantee high tip resolution and reproducibility, they have long processing times, low levels of system engineering, possible contaminants, and thermo-sensitive drugs cannot be used. In this work, a novel stamp-based microneedle fabrication method is proposed, which provides a rapid room-temperature production of multi-compartmental biodegradable polymeric microneedles for controlled intradermal drug release. Solvent casting is carried out in only a few minutes, and produces a short dissolvable tip made of polyvinylpyrrolidone (PVP). The rest of the stamp is then filled with degradable poly(lactide-co-glycolide) (PLGA) and quickly compacted with a vapor-assisted plasticization. The outcome is an array of microneedles with tunable release. The ability of the resulting microneedles to indent was assessed in a pig cadaver skin. Controlled intradermal delivery was demonstrated by loading both the tip and the body of the microneedles with a model therapeutics, POXA1b laccase from Pleurotus ostreatus, a commercial enzyme used for the whitening of skin spots. The action and indentation of the enzyme-loaded microneedle action were assessed in an in vitro skin model and highlighted their ability to control the kinetic release of the encapsulated compound.